IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD MUHAMMADIYAH PAKEM - Tukinem Tukinem; Hendro Widodo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
This research departed from the problems that arise related to the implementation of the 2013 Curriculum subjects, especially Islamic Education in Muhammadiyah Pakem Elementary School, the maximum has not been as expected. The objectives of this study are (1) to be able to find out how the implementation of the 2013 curriculum in Islamic Education subjects, (2) to find out the supporting and inhibiting factors for the implementation of the 2013 curriculum at SD Muhammadiyah Pakem. The method of this research is by unstructured interviews and direct observation. The result of this study is SD Muhammadiyah Pakem has implemented the 2013 PAI curriculum especially in the learning process, but its assessment still uses KTSP assessment. This is due to the lack of clarity related to the device or application used for the 2013 Curriculum assessment. The supporting factors for the implementation of the 2013 PAI Curriculum are the existence of adequate human resources, the existence of teachers who are mostly young and energetic. The inhibiting factor is the lack of availability of facilities and infrastructure that support the learning process, as well as the absence of the 2013 PAI curriculum assessment application. The conclusion is that the implementation of the 2013 PAI curriculum has been implemented at Muhammadiyah Pakem Elementary School in the learning process, while its assessment still uses the KTSP assessment. This is inseparable from supporting factors and the accompanying inhibitors. Keywords: implementation, Islamic education, curriculum